Innovative Approach to Furniture Production: Ecobrick Chairs as a Sustainable Solution - Benedict Ariel Kurnianto; Mieldha Hamzah Fadilah; Hendri Novendra; Taufik (Jurnal Rekayasa Sistem & Industri, 2024)
This research aims to create eco-friendly chairs using Ecobrick bottles as a base material. The excessiveuse of plastic causes a negative impact from increasing plastic waste which harms the environment andeven affects human health, especially during the COVID-19 pandemic which has led to an increase in theuse of plastic in several countries. That is the reason for the need for action to reduce plastic waste, one ofwhich is creating products made from plastic waste. The method used in this study has several stages inIdeate, Determining Customer Needs, Making Designs, Selection of Final Designs, DeterminingErgonomic Chairs, Calculation of Analysis Structures, Design Experiments and Testing, DesignRefinements, and Final Designs. From this research, it is hoped that the chairs created will be able to meetcustomer needs by having ergonomic dimensions, being environmentally friendly, and safe to use. Thisapproach is expected to provide a solution to the problem of excessive use of plastic, by turning plasticwaste into useful products and reducing the negative impact on the environment.